Galvanic lithotrophy, a new path to fuel bioelectrochemical processes - Rodríguez Simón, Carlos Norberto (2024)
Electron sources for bacterial cell processes are diverse and include water (in phototrophs) and organic (in organotrophs) and inorganic compounds (in lithotrophs). All of them share the characteristic of having a low enough oxidation–reduction potential to allow cell energy gaining when coupled to typical cell electron acceptors. While most metals and alloys have a potential low enough to serve as electron donors for bacteria, data about their direct microbial oxidation are very limited. In this work, we show that magnesium, a metal with the lowest reduction potential in the galvanic series, cannot be oxidized directly by denitrifying bacterial cells, but can serve as an electron donor when galvanically connected to them through graphite. We recognize this as a new way of accessing metal electrons for bacteria which, owing to the requirement of galvanic coupling, we propose to identify as galvanic lithotrophy. We exemplify the impact that this process may have, by showing its application to simultaneously remove nitrate, ammonium and phosphate from water, by using a readily scalable approach that allows us to recover these nutrients, in which an energy input is not required.